Factor that affect the performance of individual behavior: A case study at Hospital Kajang / Fiones Banlehong and Nor Syafiqah Mohd Isa - Banlehong, Fiones; Mohd Isa, Nor Syafiqah (Faculty of Administrative Science and Policy Studies, 2013)
An individual behavior is important aspect that needs to be considered in an organization. It can influence the organizational behavior in an organization which resulted in positive or negative behavior and also affect the performance of employees in the organization. To understand the individual behavior, MARS Model is used in this research.MARS model is a model that explains individual behavior as a result of internal and external factors of influences acting together and consists of four variables, which are, motivation, ability, role perceptions, and situational factors. The purpose of this study is to identify the factors that affect the performance of individual behavior of nurses in Hospital Kajang. The objective of this research is to identify the relationship of individual behavior on performance among nurses and to identify which variable (motivation, ability, role perception and situational factors) has a greater influence on the nurse’s performance in Hospital Kajang. Theresearchers use stratified sampling method to conduct the research. The sample size is 214 respondents which come from several department and position of nurses in Hospital Kajang. The overall findings suggest that the motivation is the most influential factors that affect the performance of nurses in Hospital Kajang.